Intranasal administration of atf protects and repairs the neonatal white matter after a cerebral hypoxic-ischemic event - Guardia Clausi, Mariano (2012)
Our previous studies showed that the intracerebral injection of apotransferrin (aTf) attenuates white matter damage and accelerates the remyelination process in a neonatal rat model of cerebral hypoxia-ischemia (HI) injury. However, the intracerebral injection of aTf might not be practical for clinical treatments. Therefore, the development of less invasive techniques capable of delivering aTf to the central nervous system would clearly aid in its effective clinical use. In this work, we have determined whether intranasal (iN) administration of human aTf provides neuroprotection to the neonatal mouse brain following a cerebral hypoxic-ischemic event. Apotransferrin was infused into the naris of neonatal mice and the HI insult was induced by right common carotid artery ligation followed by exposure to low oxygen concentration. Our results showed that aTf was successfully delivered into the neonatal HI brain and detected in the olfactory bulb, forebrain and posterior brain 30 min after inhalation. This treatment successfully reduced white matter damage, neuronal loss and astrogliosis in different brain regions and enhanced the proliferation and survival of oligodendroglial progenitor cells (OPCs) in the subventricular zone and corpus callosum (CC). Additionally, using an in vitro hypoxic model, we demonstrated that aTf prevents oligodendrocyte progenitor cell death by promoting their differentiation. In summary, these data suggest that iN administration of aTf has the potential to be used for clinical treatment to protect myelin and to induce remyelination in demyelinating hypoxic-ischemic events in the neonatal brain.